EVOLUTION OF THE RULES CORPORATE TAXATION OF CONTROLLED FOREIGN COMPANIES - GUTSALENKO, Liubov; TROKHYMETS, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes evolution of controlled foreign company (CFC) profit taxation in global practice, along with an analysis of the compliance of Ukrainian legislation with the minimum criteria established for European Union member states. The key stages of CFC taxation rule development are traced, from their introduction in the United States in 1962 to the adoption of EU Council Directive 2016/1164 (ATAD) in 2019. Special attention is given to the decision of the European Court of Justice in Cadbury Schweppes (C-196/04), which served as a catalyst for further refinement of the EU’s regulatory framework for CFC rules. The impact of the BEPS (Base Erosion and Profit Shifting) plan on the international approach to CFC profit taxation is explored. The key provisions of Ukrainian CFC legislation, introduced by Law No. 466-IX on January 16, 2020, and implemented on January 1, 2022, are clarified. The criteria under which foreign companies may be recognized as CFCs in Ukraine are identified, and the necessity of legislative improvements to align with international standards is substantiated. A comparative analysis of the requirements for CFC in Ukrainian and EU legislation has been conducted, allowing for the determination of the level of compliance of Ukrainian regulations with European standards. The issues of control over foreign companies, the mechanisms for determining tax liabilities, and the effectiveness of implementing international standards in Ukraine are set apart. The grounds for exemption from CFC profit taxation under Ukrainian legislation are also categorized. It is noted that the list of tax exemption grounds is significantly broader than the minimum requirements established for EU countries, which allowed 80% of controlling persons who submitted CFC reports to claim tax exemption in 2022 and 2023. It is concluded that further improvement of national legislation on CFC profit taxation is necessary to harmonize Ukraine’s tax policy with European standards and ensure effective control over the taxation of income earned by Ukrainian residents abroad.